Characterizing substance use and mental health profiles of cigar, blunt, and non-blunt marijuana users from the National Survey of Drug Use and Health. (1st March 2016) - Cohn, Amy; Johnson, Amanda; Ehlke, Sarah; Villanti, Andrea C.
Highlights: This study examined correlates of cigar, marijuana, and blunt use. Dual users of cigars and blunts had the most severe substance use risk profiles. Blunt users were younger, Black, and used alcohol, tobacco, and other drugs. Those who misclassified blunt and marijuana use were younger, female, and Black. Communicating risks of blunt use should be directed toward specific subgroups. Abstract: Background: Smoking marijuana in a cigar (blunt use) is gaining popularity in the U.S. Research suggests that blunt users differ from exclusive cigar or marijuana users on a variety of demographic and substance use factors. Misreporting of blunts and cigars is also common, particularly among young people, and may lead to inaccurate prevalence estimates. To determine subtype differences, this study investigated the prevalence and demographic, mental health, and substance use correlates of four mutually-exclusive groups of blunt, cigar, and marijuana past 30-day users (cigar-only, blunt-only, non-blunt marijuana, or dual cigar-blunt). Method: Data were analyzed from the 2013 National Survey of Drug Use and Health. Results: In weighted multinomial logistic regression models, respondents who were younger, Black, and who had used tobacco, alcohol, or other drugs in the past 30-days had the highest odds of reporting blunt-only or dual cigar-blunt use. Those reporting blunt-only and dual cigar-blunt use also endorsed a greater number of marijuana and alcohol use disorder symptoms compared to those reporting cigar-only and non-blunt marijuana use. Lower marijuana risk perceptions were associated with increased odds of marijuana use with or without blunts. Major depressive episode was uniquely associated with non-blunt marijuana use. With respect to misclassifiers, respondents who reported past 30-day blunt use but not past 30-day marijuana use were younger, Black, female, and had lower education and income. Discussion: Those who report blunt-only and dual cigar-blunt use showed the most severe risk profiles. Communicating health consequences and risks of blunt use should be directed toward specific subgroups.